A new hemeroscopid dragonfly (Odonata, Anisoptera) from the Lower Cretaceous of the Jiuquan Basin, northwestern China - Qi, Pengliang; Liu, Peihan; Xiao, Chuantao; Zheng, Daran (Zootaxa, 2024)
A new hemeroscopid dragonfly, Parahemeroscopus jiuquanensis gen. et sp. nov., is described from the Lower Cretaceous Zhonggou Formation of the Jiuquan Basin, northwestern China. Parahemeroscopus gen. nov. has the mixed characters of the hemeroscopid genera Hemeroscopus Pritykina, 1977 and Abrohemeroscopus Ren, Liu & Cheng, 2003, and probably represents a transitional dragonfly from Abrohemeroscopus to Hemeroscopus. The new finding not only adds to the diversity of the Hemeroscopidae Pritykina, 1977, but also provides clues for revealing the early evolution of the hemeroscopid dragonflies.